ANALISIS PENERAPAN METODE FULL COSTING DAN VARIABEL COSTING SEBAGAI PERHITUNGAN HARGA POKOK PRODUKSI DALAM PENENTUAN HARGA JUAL - Ella Mulyantie Astri (Nusantara Hasana Berdikari, 2021)
In determining the cost of production, two methods can be used, namely the full costing method and the variable costing method. In the calculation of the full costing method, all cost elements are calculated, whether variable or fixed. While the variable costing method is the determination of the cost of production which only calculates the variable cost elements. The purpose of this research is to determine the application of the full costing method and variable costing in determining the selling price. This study uses a qualitative method with a descriptive approach, this study describes the problem in depth, with the data sources used are primary data sources through observation, interviews, and documentation. The analysis technique of this research is analysis before the field where the results of the data are temporary, and further analysis during and after the field will get accurate data. Based on the research results, CV.NJ Food Industries does not apply the full costing method or variable costing in calculating the cost of production. The company uses a calculation with a simple method and does not calculate all the elements of costs for production in the cost of goods manufactured. CV.NJ Fodd Industries in determining its selling price follows the market price, this is one of the things that results in profits that are not as expected by the company.